2016
DOI: 10.4137/bcbcr.s39385
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes in Metastatic Breast Cancer: A Review of Industry-Sponsored Clinical Trials

Abstract: INTRODUCTIONPatient-reported outcome (PRO) measures serve to capture vital patient information not otherwise obtained by primary study endpoints. This paper examines how PROs are utilized as endpoints in industry-sponsored metastatic breast cancer clinical trials.METHODSA search was conducted in the clinicaltrials.gov web site for trials involving common treatments for metastatic breast cancer. Thirty-eight clinical trials were identified which included a PRO endpoint in the study, and data were extracted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Metastatic breast cancer, also known as stage IV, exhibits a higher rate of mortality than stage I disease, where the cancer is localized and has not spread to other areas of the body. In the United States between 2005 and 2011, while 98.6% of stage I patients achieved a 5‐year survival rate; only 25.9% of stage IV patients reached the same …”
Section: Breast Cancer Backgroundmentioning
confidence: 99%
“…Metastatic breast cancer, also known as stage IV, exhibits a higher rate of mortality than stage I disease, where the cancer is localized and has not spread to other areas of the body. In the United States between 2005 and 2011, while 98.6% of stage I patients achieved a 5‐year survival rate; only 25.9% of stage IV patients reached the same …”
Section: Breast Cancer Backgroundmentioning
confidence: 99%
“…Of these 13 drugs, two were approved by the EMA with PRO evaluation mentioned in their label for the treatment of MDS: azacitidine and lenalidomide. In these studies, PROs were used as secondary endpoints to assess HRQOL and the iden- [35][36][37] Our study found that PRO claims were included in the EMA- EuroQol five dimensions-three levels (EQ-5D-3L) Our study provides an initial overview of the PROM landscape in AML and MDS, which was missing in the current literature.…”
Section: Proms Included In Labels Of Approved Drugs For the Treatmementioning
confidence: 93%
“…Fatigue and reduced quality of life are frequent in patients with metastatic breast cancer related to the site of metastasis and cancer treatment [ 5 , 6 ]. Evidence from meta-analyses and systematic reviews in patients with localized breast cancer has demonstrated the benefits of physical activity on multiple health outcomes [ 7 - 12 ].…”
Section: Introductionmentioning
confidence: 99%